Cytokine levels in patients with brucellosis and their relations with the treatment - Akbulut, H.; Celik, I.; Akbulut, A. (Medknow Publications and Media Pvt. Ltd, 2007)
Purpose: To determine the serum levels of proinflammatory and some of the Th1/Th2 cytokines in brucellosis and their alterations with treatment and outcome. Methods: Twenty-eight acute and seven subacute brucellosis patients diagnosed clinically were included in the study. Twenty healthy volunteers were also included. Brucella standard tube agglutination tests and blood culture were conducted on all subjects. Cytokine levels of pre- and post-treatment period serum samples were measured by ELISA. Results: The mean serum levels of IL-6, IFN-g and TNF-a were significantly higher in brucellosis patients compared to the control group ( P < 0.05). No significant differences were found between patient and control groups in terms of IL-1? , TGF-? 1, IL-2, IL-4 and IL-8 levels. There was a positive correlation between IFN-?, TNF-? and IL-6 levels with CRP levels. IL-6, IFN-? and TNF-? levels measured after treatment were statistically significantly lower than pre-treatment values ( P < 0.001). No differences were found in the levels of these cytokines between acute and subacute patients? sera. IL-6, IFN-? and TNF-? levels were higher in acute or subacute brucellosis patients. Conclusions: Although the levels of the cytokines were decreased significantly with effective and adequate treatment these alterations did not correlate with the extent or activity of the disease.
Keywords: Brucellosis; Cytokines; Treatment